An active hybrid control approach with the Fx-RLS adaptive algorithm for active-passive isolation structures. (24th August 2020) - Yi, Sun; Junwei, Wu; Peilun, Yin; Huayan, Pu; Zhongjie, Li; Jiheng, Ding; Jun, Luo; Shaorong, Xie; Yan, Peng; Min, Wang
Abstract: With improvements in the performance of optical equipment on spacecraft, the requirements for vibration isolation have become increasingly stringent. An efficient and reliable active hybrid control (AHC) approach used for an active-passive isolation single strut (APISS) is proposed in this paper. The APISS adopts an active-passive architecture in series as one single leg of the Stewart platform. To improve performance, the AHC approach includes a modified proportional integration force (PIF) feedback control algorithm and an improved filtered-x recursive least squares (Fx-RLS) adaptive feedforward control algorithm. The PIF is applied to establish a sky-hook damping and variable mass matrix system, and Fx-RLS is employed to compensate the vibration error caused by the base platform to the payload platform. Then, a single-DOF vibration isolation system consisting of a real-time active control system and a spectrum testing and analysis system is adopted to verify the proposed approach. The experimental results indicate that the AHC approach can effectively reduce the natural frequency by 5.02 Hz. Additionally, the resonance amplitude of the natural frequency decreases by 41.84 dB, the vibration attenuation rate reaches 99.2%, and the amplitude of the mid-frequency band is further attenuated. The experimental results highlight the effectiveness of the proposed method.